Band structure and diode characteristics of transparent pn-homojunction using delafossite CuInO2. (14th October 2019) - Rahman, Hilal; Esthan, Chinnu; Nair, Bindu G; Sreeram, P R; Shinoj, V K; Behera, Prakash; Deshpande, Uday; Philip, Rachel Reena
Abstract: Technologically relevant highly rectifying all transparent delafossite pn homojunctions with CuInO2 as n-type layer and Ca doped CuInO2 as p-type layer are fabricated by oxygen plasma assisted thermal evaporation method. The best diode gives a forward to reverse current ratio ~619, which is about 62 times than that reported to date in a delafossite pn homojunction, with an ideality factor of 2.42 and a cut-in voltage of 0.87 V. Optical transmittance is 50%–70% in the visible region. Junction capacitance is in picoFarads and it is independent of frequency in the range 2 kHz to 2 MHz at a reverse voltage of 5 V. The band structure of the transparent delafossite diode is deduced for the first time by a combined analysis of the valence band spectra from x-ray photoelectron spectroscopy and the optical data.